The Effects of Poria cocos on Rho Signaling-Induced Regulation of Mobility and F-Actin Aggregation in MK-801-Treated B35 and C6 Cells - Yi-Chyan Chen; Chang-Ti Lee; Fu-Ming Tsai; Mao-Liang Chen (Behavioural Neurology)
Background and Aim. We recently investigated whether Poria cocos water extract modulates ketamine-induced Rho signaling regulation and reverses ketamine-inhibited cell mobility and F-actin reconstruction in B35 and C6 cells. Various studies have mentioned that drugs of abuse induce changes in neuronal plasticity in the brain’s reward circuitry. Modulations in neuronal plasticity are closely related to Rho signaling regulation in cells. Rho signaling has also been implicated in the addictive behavior induced by chronic opiate or morphine administration. MK-801 could induce Rho signaling regulation to further modulate cell migration and actin reorganization in neuronal and glial cells. In this study, we investigated the effects of Poria cocos water extract on Rho signal regulation in MK-801-treated B35 and C6 cells. Methods. B35 neuronal cells and C6 glial cells were incubated with MK-801 for 7 days followed by MK-801, MK801 in combination with water extracts of P. cocos (PRP for P. cocos cum Radix Pini or WP for White Poria) treatment for an additional 7 days. Analysis of cell mobility, F-actin aggregation, and Rho signaling modulation was performed to clarify the roles of PRP or WP in MK-801-treated B35 and C6 cells. Results. MK-801 decreases B35 cell mobility, whereas the inhibited cell migration ability and F-actin aggregation in MK-801-treated B35 or C6 cells could be reversed by PRP or WP. The CDC42 expression in B35 or C6 cells would be reduced by MK-801 and restored by treating with PRP or WP. The RhoA expression was increased by MK-801 in both B35 and C6 cells but was differentially regulated by PRP or WP. In B35 cells, downregulation of PFN1, N-WASP, PAK1, and ARP2/3 induced by MK-801 can be reversely modulated by PRP or WP. PRP or WP reduced the increase in the p-MLC2 expression in B35 cells treated with MK-801. The reduction in ROCK1, PFN1, p-MLC2, and ARP2/3 expression in C6 cells induced by MK-801 was restored by PRP or WP. Reduced N-WASP and PAK1 expression was differentially regulated by PRP or WP in MK-801-treated C6 cells.